The impact of microwave radiation in the processes of carbon dioxide absorption by chlorophyll-producing microalgae - Dyachok, Vasyl; Mandryk, Solomiia; Huhlych, Serhiy (Видавництво Львівської політехніки, 2020)
The influence of microwave radiation on the rate of СО2 uptake by chlorophyll-producing microalgae of the Chlorella Vulgaris has been established. Experimental dependencies of greenhouse gases absorption by microalgae depending on the impact of microwave electromagnetic (MEM) field have been obtained. The mathematical model of the dynamics of biomass growth of Chlorella Vulgaris microalgae depending on the time of electromagnetic radiation has been constructed. Based on the mathematical model solution and the experimental data obtained, a chart of the dependence of CO2 absorption by microalgae of the Chlorella Vulgaris provided that microwave radiation is present, has been constructed. The optimal value of microwave electromagnetic radiation for the design of technological schemes for the industrial purification of gas emissions from carbon dioxide by biological method has been established.
Keywords: photosynthesis; electromagnetic radiation; Chlorella Vulgaris; biomass dynamics; mathematical model; kinetics